Las colecciones de referencia en el contexto de una arqueología social (2011)
ABSTRACT: This article present a critic revision on the role that archeological laboratories and reference collections play in getting local society and archeology. The analysis aims to gives a current perspective about the archeological records as a valuable patrimony of a nation, especially in fields such as International cultural policies and local territorial and developmental plans. This revision is based on the archeological collection of the University of Antioquia in Colombia.